DO ISLAMIC GREEN FINANCE AND REGULATORY GOVERNANCE DRIVE ENVIRONMENTAL SUSTAINABILITY? PERSPECTIVES FROM MUSLIM-MAJORITY COUNTRIES - Basri Basri; Endra Kasni Laila Yuda; Syahrul Gunawan; Akmal Asman (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2026)
Introduction: This study aims to analyze the dynamic impact of GDP per capita, Regulatory Quality, Islamic Green Finance (IGF), and Oil Revenue on sustainable economic performance in Islamic countries. Methods: Using panel data from 24 OIC member countries over 2012–2023, this study applies the Panel Autoregressive Distributed Lag (ARDL) model to distinguish short-run adjustments and long-run equilibrium relationships. Results: Regulatory Quality is a significant positive determinant in the long run under the Dynamic Fixed Effects (DFE) estimator. The Error Correction Term (ECT) is negative and significant, indicating stable adjustment toward long-run equilibrium. Short-run country-specific analysis shows heterogeneous effects: Regulatory Quality positively influences Iran and Iraq, while IGF demonstrates varying impacts in Bahrain and Malaysia. Conclusion and suggestion: Strengthening institutional governance and implementing context-specific green finance policies are essential to enhance sustainable economic resilience in OIC countries. Policymakers should balance resource dependence with financial and regulatory innovation.